Konsep Kosmologi Dalam Filsafat - Fathur Rahman (TASAMUH: Jurnal Studi Islam, 2016)
The discussion about the creation in the study of the philosophers usually is incorporated into the discussion of cosmology. Cosmology is a part of natural philosophy in which the core discusses natural, natural contents and their relationship with each other and with existing existence with absolute. Advanced study of the origin of the universe called cosmogony, now by modern astronomers, cosmogony study the origin and evolution of the universe has expanded into cosmology. Study cosmos of this study is the universe and the objects contained in it that are associated include integration and relations “Three reality” between Gods, the macrocosm and microcosm. Macrocosm term is synonymous with the world that is defined by everything other than Allah. So the use of the term usually is a substitute microcosm macrocosm. Microcosm is a human individual who symbolizes all the qualities that were found in God. So it is natural or whole cosmos is God’s creatures, which include various planets and everything in it is the human individual and social, living and inanimate objects. This article describes the world of cosmology in the view of philosophy